Demographic and clinical spectrum of sinonasal masses in a tertiary care centre - Gupta, Abhishek Kumar; Swarnakar, Neha; Armo, Usha; Singh, B. R.; Gupta, Shailendra; Minj, Anupam; Damle, G. K. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Sinonasal masses constitute a wide spectrum of pathologies, ranging from benign polyps to malignant tumors. Their clinical presentations and demographic distributions vary significantly across regions. This study evaluates the demographic profile, clinical spectrum, and preliminary histopathological correlation of sinonasal masses in patients presenting to a tertiary care center in central India Methods: A prospective observational study was conducted over 24 months on 162 patients with clinical and radiological features of sinonasal masses. Data on age, gender, residence, socioeconomic status, symptoms, side of involvement, provisional diagnosis, and histopathology were analyzed. Results: Most patients were aged 19–30 years (56.3%), with a male predominance (53.1%). Nasal obstruction was the most common symptom (88%), followed by anosmia (42%), headache (36%), rhinorrhea (33%), and epistaxis (13%). Rural residents accounted for 67.3% of cases. The majority were benign lesions, with Allergic polyps (40.1%) being most common. Unilateral presentation (59.2%) was significantly associated with neoplastic pathologies. Conclusions: Sinonasal masses predominantly affect young rural adults. Clinical evaluation, supported by imaging and endoscopy, is vital for diagnosis. Public health efforts should emphasize early ENT screening and accessibility in rural populations.